Efficacy and onset of action of fluticasone propionate aqueous nasal spray on nasal symptoms, eosinophil count, and mediator release after nasal allergen challenge in patients with seasonal allergic rhinitis - Wang, D. (2014)
Allergy: European Journal of Allergy and Clinical Immunology